US–Colombia Free Trade Agreement: What Is in It for Florida Agriculture? - Edward A. Evans; Fredy H. Ballen (EDIS)
On October 12, 2011, the US Congress ratified a Free Trade Agreement/Trade Promotion Agreement (FTA) with Colombia, five years after it was signed by President George W. Bush. The FTA took effect in May of 2012. This 13-page fact sheet highlights the key elements of the US Colombia FTA as they relate to trade in agricultural commodities, and to examine what is at stake for Florida. Written by Edward A. Evans and Fredy H. Ballen, and published by the UF Department of Food and Resource Economics, July 2012.